Kegiatan Pos Pelayanan Terpadu (Posyandu) Balita dan Lansia Di Desa Karang Indah - Noor Hidayah; Muhammad Rezky Noor Handy; Mutiani Mutiani; Muhammad Adhitya Hidayat Putra; Sigit Triyono (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
Lack of public awareness of the importance of health by living a healthy lifestyle. Therefore, posyandu cadres in Karang Indah village can build public awareness about the importance of health and strengthen the Karang Indah village community by making it easier for people to access health services. This article describes the posyandu activities in Karang Indah Village and the various obstacles posyandu officers face in Karang Indah Village. This research uses a descriptive qualitative approach. The data collection techniques used were observation, interviews and documentation. The instrument for this research is the researcher, who creates observation and interview guidelines and determines sources. The data analysis techniques used include data reduction, data presentation and conclusions. The research results specifically explain that the posyandu program consists of primary activities, which include Maternal and Child Health, Family Planning, Preventing Polio in Children with immunizations, Monitoring Nutritional Status, and Prevention and Management of Diarrhea. The Posyandu for toddlers consists of several activities as follows: Filling out the attendance list for toddlers, measuring the weight and height of toddlers, immunizations and providing vitamins for toddlers, while the activities of the Elderly Posyandu consist of Weighing older people, checking the elderly's blood pressure, exercising the elderly's memory, and exercising for the elderly. The problem faced by Posyandu officers is the lack of facilities, which are still in a multi-purpose building in Karang Indah Village.